Polarisation‐independent wavelength filter using Si wire waveguide Bragg grating and multimode interference couplers. Issue 5 (1st February 2014) - Okayama, H.; Onawa, Y.; Shimura, D.; Takahashi, H.; Miyamura, S.; Yaegashi, H.; Sasaki, H.
Abstract : A wavelength filter using Si wire waveguide Bragg grating and multimode interference couplers is reported. The device is designed for the optical network unit of the fibre to the home system. All the components are designed to achieve polarisation independence.